Intrapreneurial behavior: an empirical investigation of personality traits - Muhammad, Farrukh; Chong, Wei Ying; Shaheen, Mansori (2016)
The study investigated the impact of personality traits on intrapreneurial behavior. Data was collected from 306 employees working in higher education institutions. Structural equation modeling technique was utilized with the help of SmartPLS software. The findings of the study revealed a positive association of extroversion, openness to experiences and emotional stability with intrapreneurial behavior, while a negative impact of conscientiousness, agreeableness on intrapreneurial behavior was recorded. The findings of this study have several implications in the context of HEIs. To enhance the intrapreneurial behavior in the higher educational institutes, the management of the institutions should take positive steps to ensure that employees have personality traits which have shown a significant impact on the intraprenuerial behavior in this study. One strategy top management could consider is that, at the time of recruitment, preference should be given to candidates with higher levels of extroversion, openness to experience and emotional stability. However, among all the traits, the most indicative marker is extroversions followed by emotional stability. Therefore, hiring employees with high levels of extroversion and emotional stability could facilitate more intraprenuerial behavior, which ultimately, will help improve the performance of HEIs. This study with its focus on the micro level foundations of intrapreneurial behavior is one of the first studies in the domain of intrapreneurship.